Miltefosina no Tratamento de Cães com Leishmaniose: Efeitos Hematológicos e Bioquímicos. - Santos, Shammara Noleto (2023)
Canine visceral leishmaniasis (CVL) is an infectious disease caused by a protozoan belonging to the genus Leishmania. It is an anthropozoonosis of enormous importance due to the increase in the human mortality rate in the regions considered endemic, the large number of infected dogs and the intense parasitism of these animals. The release of miltefosine (Milteforan®) by the Ministério da Agricultura Pecuária e Abastecimenco (MAPA) for treatment of the animals took place in October 2016; this drug has been used in the USA and Europe for several years and with good results. A total of 20 dogs were evaluated, 10 of which belonged to group 1 (G1), treated with miltefosine, and group 2 (G2), with 10 animals without treatment. The data were collected in two moments called (M1) and (M2), being at pre and post treatment respectively. The objective was to evaluate the hematological and biochemical effects of serum in response to treatment, observing possible effects on these parameters. The main hematological changes were: low hemoglobin, red blood cells and hematocrit that characterized anemia. In the hematology, there was a significant statistical difference between the pre and post treatment in the hematocrit and platelet values, with an increase on these values. In the biochemical exams, there were significant alterations to the parameters: alaninoaspartatetransferase and globulins, causing a decrease in mean values, albumin and albumin / globulin ratio increased their values. Dogs receiving treatment with miltefosine showed clinical improvement and hepatotoxic and nephrotoxic effects were not observed.